Dementia and Cognitive Impairment Among U.S. Veterans With a History of MDD or PTSD: A Retrospective Cohort Study Based on Sex and Race. (September 2019) - Bhattarai, Jagriti "Jackie"; Oehlert, Mary E.; Multon, Karen D.; Sumerall, Scott W.
Objective: The aim of this study was to examine major depressive disorder (MDD) and posttraumatic stress disorder (PTSD) diagnosed at age < 55 as predictors, and sex and race as potential moderators, of dementia and other forms of cognitive impairment.Method: Veterans ( N = 4, 800) aged ⩾ 56 years were grouped by psychiatric history, sex, and race. Hierarchical and stepwise regression were employed to determine significant predictors.Results: MDD and PTSD were associated with almost double the risk for developing dementia or cognitive impairment at age ⩾ 56. Sex, as a moderator, had small effects whereas race increased the risk almost twofold for Black veterans, given the presence of MDD history.Discussion: MDD and PTSD act as significant risk factors for dementia and other forms of cognitive impairment, and Black veterans, given a history of MDD, may be at an increased risk. An important endeavor for future research is to examine how this risk may vary across dementia subtypes and related conditions.